2008
DOI: 10.1073/pnas.0805154105
|View full text |Cite
|
Sign up to set email alerts
|

Identification of reptilian genes encoding hair keratin-like proteins suggests a new scenario for the evolutionary origin of hair

Abstract: The appearance of hair is one of the main evolutionary innovations in the amniote lineage leading to mammals. The main components of mammalian hair are cysteine-rich type I and type II keratins, also known as hard ␣-keratins or ''hair keratins.'' To determine the evolutionary history of these important structural proteins, we compared the genomic loci of the human hair keratin genes with the homologous loci of the chicken and of the green anole lizard Anolis carolinenis. The genome of the chicken contained one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(137 citation statements)
references
References 32 publications
2
135
0
Order By: Relevance
“…1C and Table 1). Recent studies have shown that the latter seems to represent the most primitive type II hair keratin as K84 homologues have been detected in the claws of lizards (17). Remarkably, but compatible with its position in the phylogenetic tree, the non-␣-helical domains of the K80 neighbor K78 (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…1C and Table 1). Recent studies have shown that the latter seems to represent the most primitive type II hair keratin as K84 homologues have been detected in the claws of lizards (17). Remarkably, but compatible with its position in the phylogenetic tree, the non-␣-helical domains of the K80 neighbor K78 (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…[11][12][13] Our recent studies have suggested that SFTPs originated prior to the diversification of amniotes (mammals, reptiles and birds). [14][15][16] However, the evolutionary origin of SFTPs has remained uncertain because of incomplete genome data of the next relatives of amniotes, the amphibians.…”
Section: Questions Addressedmentioning
confidence: 99%
“…Although these fractions were determined on a keratins (Alexander & Earland 1950;Gillespie et al 1968;Lindley & Cranston 1974), we believed, as implied by some workers (Wainwright et al 1976), that the fractions might be similar in b keratins. We mention in parentheses subsequent research (Eckhart et al 2008) that shows that cysteine-rich a keratins are not restricted to mammals and that the evolution of mammalian hair may have involved the cooption of pre-existing structural proteins (lizards and birds) and, interestingly, that in the keratins in lizard claws there were sulphur -sulphur bonds unrelated to mammalian counterparts.…”
Section: Introductionmentioning
confidence: 99%